Animação em stop-motion: tecnologia de produção através da história - Thiago Franco Ribeiro (2009)
The aim of this study is to analyze the technological processes ofproductions in stop-motion animation through the history, trying to establish the major apparatus and the technical development, which helped to make these models of animation viable, concerning marketing, and better regarding technical quality. Many were the film directors, even inserted in the model of stop-motion animation market, who achieved a production methodology and instituted, about tests in the use of materials, animation and manipulation of the image, advanced technical approaches, systematically modern, to the animation entertainment as stop-motion. The study of the experiences and searches for new technologies in stop-motion animation is fundamental to the better comprehension of the entire elaboration of this production model, as constituting detailed information about the whole work in studio, approaching different production archetypes along the stop-motion animation history. Therefore, with reference to researches in technology of production, both in materials as in equipments, the overview about the structure is able to improve the structures of the independent realizations, allowing the knowledge about a market with a great potential, strongly broadcasted in different societies and industry and that grows more and more in productions, the stop-motion animation.